DEVELOPING AN INSTRUMENT FOR ASSESSING THE PHYSICS COGNITIVE LEARNING ACHIEVEMENT OF HIGH SCHOOL STUDENTS THROUGH LOCAL WISDOM-BASED FIELDWORK - Annisa, Azza Ismu; Mundilarto, Mundilarto (SCAD Independent, 2020)
This study aims to reveal (1) the construct and (2) the characteristics of the developed instrument for assessing Physics cognitive learning achievement of high school students in outdoor learning models through local wisdom-based fieldwork. This research was a research and development using the approach developed by Mardapi (2012: 110). The steps taken included (1) preparing instrument specifications, (2) writing the instrument, (3) reviewing the instrument, (4) doing instrument trial, (5) analyzing the instrument, (6) improving the instrument, assemble the test (8) implementing the test, and (9) interpreting measurement result. The results of the study showed that the  Instrument of cognitive skills consisted of 50 items with two-tier multiple choices focused on indicators of cognitive skills. The instrument was categorized fit the PCM 1PL and the difficulty level of the items ranges from -1,00 to 1,22 which means the items were in a good category. The reliability of the items was 0,89 for the ability ranging from -2 to 2 with standard error measurement 0,23, which means it was in a very high category.